PHYSICAL CHEMISTRYAND MICROBIOLOGY OF ETAWAH CROSSBREED GOAT MILK DURING STORAGE AT ROOM TEMPERATURE - Y.D.A., Anggreani; Mariani, N.P.; Okarini, I.A. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
Fresh goat's milk has more complete nutrition and some bioactive components that play a role in maintaining body health, but leng storage at room temperature will affect the nutritional content and level of food safety. An important aspect in assessing milk quality is physical chemistry and microbiological properties, therefore this study aims to determine the physical chemistry and microbiological milk of Etawah Crossbreeds goats during storage at room temperature. The study was conducted from 29 June to 2 August 2018. The milk used in this study was Etawah Crossbreed goat milk which was obtained in Sepang Village, Buleleng Regency. The experimental design used was a Completely Randomized Design with three treatments and four replications. The research treatment was fresh goat milk stored at room temperature for 0 hour (P 0 ); 4 hours (P 4 ) and 6 hours (P 6 ). The variables observed were aroma tests, pH values, Solid Non Fat (SNF) levels and total E. coli bacteria. The results showed that with the longer storage time (P 0 , P 4 and P 6 ) the pH value showed no significant difference (P>0.05), while the storage times of P 4 and P 6 were in the aroma test respectively (21.53% and 37.02%) and total E. coli bacteria (18.73% and 41.69%) lower than P 0 which showed a significant decrease (P<0.05). SNF levels increased significantly (P<0.05), where P 4 (9.83%) and P 6 (8.35%) were higher than P 0 . Based on this study it can be concluded that the storage time resulted in a marked decrease in the value of aroma preference and total E. coli bacteria, while SNF levels was very significant increase and the pH value did not depend on the length of storage. Keywords: Quality of PE goat milk, storage, physicochemistry, microbiology